A fractal crazing constitutive model of glassy polymers considering damage and toughening. (15th May 2022) - Li, Yong; Sun, Xunhua; Zhang, Shoudong; Han, Shanling
Highlights: For the first time, A fractal evolution framework of creep crazing is established. A new craze variable describes both damage and toughening by the fractal theory. A novel fractal dimension calculation method is modified by area transformation. The fractal dimension of PMMA creep is linear with stress and exponential with time. The model explains three differences between the craze and microcrack. Abstract: Mechanical properties of crazed polymers are the competitive result between damage and toughening. Firstly, the fractal dimension interval of the planar crazes is proved to be [0, 2), and the craze variable is proposed to characterize the joint effect of damage and toughening by the fractal dimension. Then, a new fractal dimension calculation method is defined by area transformation under finite deformation, and the corresponding craze variable is modified to eliminate the influence of elastic and plastic deformation. So, the fractal crazing constitutive model was established. Thirdly, creep tests of PMMA show that the stress threshold of crazing decreases exponentially with time and eventually tends to be constant, and its fractal dimension is linear with stress and exponential with time. And the parameters of the damage equation are determined, which illustrates that the craze variable can not only explain the fractal discontinuity and strain continuity of craze but also explain three differences between the craze and microcrack. At last, the theoretical curve proved that the model was following the experimental results. For the first time, the crazing evolutionary framework of creep of glassy polymers is established and validated by the fractal theory.